Intuitive vs. Analytical Mode of Information Processing: The News Broadcast Decisions Context - Aydın, Alperen Mehmet (Information World, 2017)
This research is about decision-making behaviour of news editors. In social settings, situation shapes the human behaviour. Accordingly, editorial decisions for news production and broadcast are bounded with the situation. The objective of the research is to illuminate the use of intuition and analytical process for news decisions. Qualitative methodology was used for the fieldwork. Interviews were conducted with seventeen journalists. Cultural Historical Activity Theory is used as a theoretical framework and methodological tool. Findings reveal that editors use both intuition and analytical methods for decisions. Varying situations significantly alter the editors’ way of making news broadcast decisions.